Peningkatan Penguasaan Metodologi Penelitian Kualitatif Secara Komprehensif Mahasiswa Melalui Dekonstruksi Model Ucapan Idul Fitri - Bagus Haryono; Sudarmo Sudarmo; Triyanto Triyanto; Brq Dagfa Inka Mahadika (Society, 2023)
This quasi-experimental study aims to enhance the Mastery of Comprehensive Qualitative Research Methodology (MCQRM) among Sociology students. The goal is to equip students with systematic thinking steps involving philosophy, paradigm, object of study, theory, method, statistics, case examples, and addressing real problems and solutions. The research adopts a deconstruction approach, using the model of Eid al-Fitr greetings as its substance. The participants are 26 Sociology students enrolled in the Qualitative Research Method course. Data was collected through surveys using Google Forms twice during sessions from the 9th to the 15th meeting. Responses from the first form were compared with those from the second form. The differences between them were then interpreted as indicators of changes in the mastery of comprehensive thinking steps resulting from the learning treatment. The data were analyzed using analytical descriptive statistics in SPSS software. The results show a significant improvement in the overall mastery of qualitative research methodology, with a positive change of 30.8%. Improvement is also evident in method mastery at 38.5% and statistical mastery at 11.5%. The students successfully construct comprehensive thinking steps, ranging from post-positivism philosophy to the application of social definition and social behavior paradigms. They can understand the object of sociological study in cognitive, affective, and psychomotor dimensions, integrating Action and Social Exchange theories, Qualitative Research Methods, and descriptive statistics. Through this understanding, students can present a fluent thought process from various philosophical perspectives and in solving real-world problems.